ANALISA TINGKAT KEPUASAN PELANGGAN TERHADAP PELAYANAN HOTEL ADIMULIA MEDAN - Ir. Omry Pangaribuan, MM (LPPM ISTP, 2019)
This study aims to determine and determine the level of customer satisfaction with the performance of Adimulia Medan Hotel services, find out the level of suitability between Adimulia Medan Hotel services with customer expectations and know the factors that need to be prioritized and which need to be maintained in the Adimulia Medan Hotel Services. This research is a survey research using cross sectional design, data collection instruments in this study are questionnaires. The number of respondents in the study was 100 respondents. Data processing and analysis using Importane Performance Analysis (IPA) Cartesian and statistical diagrams with the help of data calculation / processing using SPSS version 6. From the results of data processing and analysis, the following conclusions are obtained: The level of customer satisfaction with the performance / implementation carried out by Hotel Adimulia Medan , is an average of 97.77%. The average suitability level between Adimulia Hotel Medan services and customer expectations is 91.83%.